MANIFESTAÇÕES DA FÉ CATÓLICA: um estudo sobre as festas de Nossa Senhora dos Remédios, Nossa Senhora da Conceição e Nossa Senhora do Rosário em São Luís (1850- 1875). - OLIVEIRA, Milena Rodrigues de (2016)
This study researched the main religious festivals that took place in São Luís in the 1850 period to 1875, religious festivals encompassed three stages, the first was the Mass that took place within the Church, the second was the procession and the third involved party off, this study decided to study in more detail the second and third stage of the festival, among the parties have chosen three to specify in more detail on specific chapters, these were Our Lady of Remedios that was frequented by merchants, Our Lady of the Rosary I accepted slaves and Our Lady of the Conception who accepted free and brown. The period 1850-1875 was chosen by the availability of documentation and the greater control that the Catholic Church decided to carry on his devotees in the second half of the nineteenth century, used as appointments reference, which were documents regulating the administration of the brotherhoods, newspapers, collection laws and even pastoral letters, for a better foundation on the subject also left for a literature that has helped us to further deepen our object.